Risks, Ex-ante Actions and Public Assistance : Impacts of Natural Disasters on Child Schooling in Bangladesh, Ethiopia and Malawi - Yamauchi, Futoshi; Yohannes, Yisehac; Quisumbing, Agnes (2012)
This paper examines the impacts of natural disasters on schooling investments with special focus on the roles of ex-ante actions and ex-post responses using panel data from Bangladesh, Ethiopia, and Malawi. The importance of ex-ante actions depends on disaster risks and the likelihood of public assistance, which potentially creates substitution between the two actions. The findings show that higher future probabilities of disasters increase the likelihood of holding more human capital and/or livestock relative to land, and this asset-portfolio effect is significant in disaster prone areas. The empirical results support the roles of both ex-ante and ex-post responses (public assistance) in coping with disasters, but also show interesting variations across countries. In Ethiopia, public assistance plays a more important role than ex-ante actions to mitigate the impact of shocks on child schooling. In contrast, households in Malawi rely more on private ex-ante actions than public assistance. The Bangladesh example shows active roles of both ex-ante and ex-post actions. These observations are consistent with the finding on the relationship between ex-ante actions and disaster risks. The results also show that among ex-ante actions, human capital accumulated in the household prior to disasters helps mitigate the negative effects of disasters in both the short and long runs.